DEVELOPMENT AND JUSTIFICATION OF THE MAIN PARAMETERS OF THE PROTECTANT OF PUBESCENT COTTON SEEDS (Web of Technology: Multidimensional Research Journal, 2024)
The article presents the results of theoretical studies to substantiate the optimal height of the protrusion of the teeth of the saw cylinder, depending on the required seed productivity, and presents an analytical method for determining the parameters of the seed capture and dragging zone based on the seed equilibrium condition in the space between the teeth of the drum. The parameters of the drum tooth and the height of the tooth protrusion from the grate are recommended, both ensuring the appropriate efficiency of seed etching. The dependencies describing the movement of seeds on an inclined tray are also theoretically considered and derived, and the recommended angles of inclination of the tray depending on the angle of friction of the seeds are given.